Stabilization of canthaxanthin produced by Dietzia natronolimnaea HS-1 with spray drying microencapsulation - Hojjati, Mohammad (Springer India, 2012)
The strain bacterium Dietzia natronolimnaea has propounded as a source for biological production of canthaxanthin. Because of sensitivity of this pigment, examine on its stability is important. In this study, stability of encapsulated canthaxanthin from D. natronolimnaea HS-1 using soluble soybean polysaccharide (SSPS), gum acacia (GA), and maltodextrin (MD) as wall materials was investigated at 4, 25, and 45 °C in light and dark conditions during 4 months of storage. It was shown that the type of walls influenced the size of emulsion droplets; spray dried particles, microencapsulation efficiency (ME), and retention of canthaxanthin in microcapsules. SSPS and MD produced the smallest and the biggest emulsion droplets and spray dried particles, respectively. Microcapsules made with SSPS resulted in better ME and higher stability for canthaxanthin. Samples were degraded in all conditions, especially in light and 45 °C. Degradation of microencapsulated canthaxanthin with SSPS and GA proceeded more slowly than did with MD. Regardless of the type of wall materials, total canthaxanthin contents of the microencapsulated products decreased by an increase in time or temperature. Also, samples exposed to light indicated less stability at 4 and 25 °C when compared to the storage at dark conditions. According to the results of this study, SSPS can be considered as potential wall material for the encapsulation of carotenoids.